Diphenyl-tetrazol-propanamide Derivatives Act as Dual-Specific Antagonists of Platelet CLEC-2 and Glycoprotein VI - Watanabe, Nobuo; Shinozaki, Yoshiko; Ogiwara, Sanae; Miyagasako, Riko; Sasaki, Ayumi; Kato, Junko; Suzuki, Yusuke; Fukunishi, Natsuko; Okada, Yoshinori; Saito, Takeshi; Iida, Yumi; Higashiseto, Misaki; Masuda, Haruchika; Nagata, Eiichiro; Gotoh, Kazuhito; Amino, Mari; Tsuji, Tomoatsu; Morita, Seiji; Nakagawa, Yoshihide; Hirayama, Noriaki; Inokuchi, Sadaki (Thrombosis and Haemostasis, 2023)
Background Platelet C-type lectin-like receptor 2 (CLEC-2) induces platelet activation and aggregation after clustering by its ligand podoplanin (PDPN). PDPN, which is not normally expressed in cells in contact with blood flow, is induced in inflammatory immune cells and some malignant tumor cells, thereby increasing the risk of venous thromboembolism (VTE) and tumor metastasis. Therefore, small-molecule compounds that can interfere with the PDPN–CLEC-2 axis have the potential to become selective antiplatelet agents.Methods and Results Using molecular docking analysis of CLEC-2 and a PDPN–CLEC-2 binding-inhibition assay, we identified a group of diphenyl-tetrazol-propanamide derivatives as novel CLEC-2 inhibitors. A total of 12 hit compounds also inhibited PDPN-induced platelet aggregation in humans and mice. Unexpectedly, these compounds also fit the collagen-binding pocket of the glycoprotein VI molecule, thereby inhibiting collagen interaction. These compounds also inhibited collagen-induced platelet aggregation, and one compound ameliorated collagen-induced thrombocytopenia in mice. For clinical use, these compounds will require a degree of chemical modification to decrease albumin binding.Conclusion Nonetheless, as dual activation of platelets by collagen and PDPN-positive cells is expected to occur after the rupture of atherosclerotic plaques, these dual antagonists could represent a promising pharmacophore, particularly for arterial thrombosis, in addition to VTE and metastasis.
Keywords: tumor metastasis; thrombosis; stroke; myocardial infarction